Analiza wskaźników funkcjonowania Biblioteki Uniwersyteckiej w Poznaniu za lata 2002-2006, dla potrzeb projektu standaryzacji działań bibliotek naukowych w Polsce - Wesolowska-Mis, Hanna; Jazdon, Artur (Biblioteka Uniwersytecka w Poznaniu, 2007)
The article discusses the results of the analysis of the norms and standards for functioning of Poznań University Library and includes a juxtaposition of their mean values with corresponding values in other university libraries obtained during an electronic survey carried out within the project of standardization of professional activities of research and university libraries in Poland for the years 2002-2006.
The analysis of the norms and standards for functioning of Poznań University Library for the years 2002-2006, supporting information for the project of library procedures standardisation in Polish research libraries